Evaluate the Use of Peripheral Venous Blood Alone in Formation of New Bone Under the Maxillary Sinus Membrane (Journal of Hama University, 2020)
The Purpose of this study to review the literature associated with new bone formation in the maxillary sinus elevation using peripheral venous blood alone. A review of the literature was performed to record the study reference, design study, sinus lift method, number of patients, number of implants, follow up, bone gain and Perforation of sinus. A PubMed search was made from 2007 to 2017 with keywords: “sinus lift”, “Peripheral Venous Blood”, “new bone” and “maxillary sinus elevation”. 11 articles  were identified and reviewed. The Lateral Window method was followed in all the studied publications. The survival rate of implants was high in all cases. A new bone is formed in most cases. According to our review, the application of bone graft material may not be a requirement for maxillary sinus augmentation and new bone formation with peripheral venous blood as a filler material could be an alternative treatment modality for the implant treatment.